COMPARISON OF GRAMMAR TRANSLATION METHOD AND ECLECTIC METHOD IN ENHANCING STUDENTS’ VOCABULARY ACHIEVEMENT - Caroline V. Katemba; Grace Hulu; Nelson Panjaitan (Fakultas Keguruan dan Ilmu Pendidikan Universitas Advent Indonesia, 2011)
In teaching language there are some factors that should be considered in orderto make the teaching learning process work and reach the success. The teacher should knowhow to make the language teaching effective, who the learners are, the method and techniquethat is suitable with the need of the learners and the condition of the classroom.Due to the reason above, this study entitled “Comparison of Grammar Translation method andEclectic Method in Enhancing Students Vocabulary Achievement” was employed toinvestigate and examine their difference in teaching vocabulary to the early students.The participants involved in this study were grade 4 students of KaryawangiElementary School Parongpong Bandung. This study has three major activities that wereinvolved. They were: Pretest, implementation of Grammar Translation method and EclecticMethod and post test. The participants were commanded to answer the multiple choice test inpre test and post test. During the implementation, the participants were taught vocabulary byusing the different method for each group.This research obtained data follows: n1=27, n2=33, Î±=0.05, mean difference ofGrammar Translation Method was 19.22 where mean difference for the Eclectic group was22.29. After the treatment it was obtained that the mean of post test of Grammar group were57.14 and for the Eclectic group the mean of post test were 60.21.From mean of gain of the post test result (The result show that tobserved > ttable: 2.9 >1.645), it can be concluded that the mean of gain of Eclectic group is higher than the mean ofGrammar Translation Method students’ vocabulary achievement and Eclectic methodstudents’ vocabulary achievement.